Alcohol use and alcohol-related consequences are associated with not being virally suppressed among persons living with HIV in the Rakai region of Uganda - Miller, Amanda P.; Pitpitan, Eileen V.; Kiene, Susan M.; Raj, Anita; Jain, Sonia; Luisa Zuniga, Marıa; Nabulaku, Dorean; Nalugoda, Fred; Ssekubugu, Robert; Nantume, Betty; Kigozi, Godfrey; Sewankambo, Nelson K.; et al. (Drug and Alcohol Dependence, 2021)
Background: Alcohol use is common among persons living with HIV (PWH) in Uganda and associated with poor HIV care outcomes; findings regarding the relationship between alcohol use and viral suppression (VS) have been inconclusive. Methods: Data from two rounds (2017-2020) of the Rakai Community Cohort Study, an open population-based cohort study in the Rakai region, Uganda, were analyzed. Two alcohol exposures were explored: past year alcohol use and alcohol-related consequences. Multivariable models (GEE) were used to estimate associations between alcohol exposures and VS for the overall sample and stratified by sex, adjusting for repeated measurement. Causal mediation by ART use was explored. Results: Over half (55%) of participants (n=3,823 PWH) reported alcohol use at baseline; 37.8% of those reporting alcohol use reported alcohol-related consequences. ART use and VS at baseline significantly differed by alcohol use with person reporting alcohol use being less likely to be on ART or VS. Alcohol use was significantly associated with decreased odds of VS among women but not men (adj. OR 0.72 95% CI 0.58-0.89, p=0.0031). However, among males who use alcohol, experiencing alcohol-related consequences was significantly associated with decreased odds of VS (adj. OR 0.69 95% CI 0.54-0.88, p=0.0034). The relationships between both alcohol exposures and VS were not significant in models restricted to persons on ART. Conclusions: We provide sex-stratified estimates of associations between two alcohol measures and VS in the context of current HIV treatment guidelines. This study confirms that alcohol use is adversely associated with VS but ART use mediates this pathway, suggesting that initiation and retention on ART are critical steps to addressing alcohol-related disparities in VS.
Keywords: Uganda; Alcohol; HIV care continuum; Viral suppression; Treatment adherence